Urinary IL-6: a marker for mesangial proliferative glomerulonephritis? - Gordon, C (1991)
A prospective study of plasma and urinary interleukin-6 (IL-6) levels was performed in 54 patients undergoing renal biopsy to determine whether detectable urinary IL-6 was a reliable marker for mesangial proliferation. Interleukin-6 was found in both the urine and plasma of seven patients, the urine alone of 15 patients, and the plasma alone of two patients. Interleukin-6 was not detected in the urine or the plasma of the remaining 30 patients, the urine of 10 healthy controls or the urine of 10 patients with rheumatoid arthritis with raised plasma IL-6. Interleukin-6 was found in the urine of only one out of an additional seven patients with lupus nephritis. Urinary IL-6 was associated with a variety of renal abnormalities and was not restricted to those with mesangial hypercellularity. Furthermore, many patients with mesangial hypercellularity did not have detectable urinary IL-6. There was no correlation between urinary IL-6 and plasma IL-6, urinary albumin excretion or urinary creatinine. These results suggest that IL-6 detected in the urine is a marker of renal IL-6 production, but not specifically of mesangial hypercellularity. The patients with IL-6 in the urine had a mean serum creatinine significantly higher than those without IL-6. It is not possible to distinguish at present whether IL-6 contributes to renal dysfunction or whether it reflects renal damage.